The Effect of TikTok Live Streaming Shopping on Impulse Buying Behavior in The 2023 Global Crisis - Ardiyanti, Vika Diyah (Universitas Diponegoro, 2023)
Various studies have proven the effectiveness of social media in influencing consumers. This is used by business actors to increase sales through social media. Especially now that entertainment media such as Tiktok also provide convenience by presenting the Tiktok shop and Tiktok live streaming shopping. The presence of TikTok live streaming shopping is increasingly spoiling TikTok users. In fact, many potential consumers who had no previous shopping plans suddenly made a purchase. This is called impulsive buying. Impulse behavior is certainly not wise to do during a global crisis like today. The decline in income levels requires people to downsize. This study aims to determine the effect of tiktok live streaming shopping on impulsive buying behavior in the era of the global crisis. From the results of research conducted on 100 sample people using a qualitative descriptive method, it shows that tiktok live streaming shopping has a significant effect of 38.5% on impulsive buying behavior. This is due to the affordable product selling prices, ease of communication between sellers and buyers, as well as attractive promos such as special prices when shopping during live streaming.